The effect of product quality and brand image on purchase decisions - Siti Nurhasanah; Ismartaya Ismartaya; Endang Silaningsih (Universitas Nusa Cendana, 2026)
Among MS Glow's Leles branch customers, this research looks at how product quality and brand image affect purchasing choices. Improving market positioning and maintaining customer loyalty in the fiercely competitive cosmetics sector requires a deep knowledge of consumer purchase behaviour variables. Using multiple linear regression analysis, this quantitative study examines the connection between product quality, brand image, and purchasing choices. One hundred MS Glow customers were polled using standardised questionnaires, and the results were evaluated via statistical methods. Both product quality and brand image have a favourable and substantial impact on customers' purchase choices, according to the data. A strong and positive brand image boosts customer confidence and buy intention, while high-quality goods promote consumer trust and satisfaction. The findings show that when choosing skincare products, customers care a lot about how the product works and how they feel about the brand. The significance of ongoing product innovation and strong brand management in gaining a competitive edge in the skincare and cosmetics industry is highlighted by these results. By offering data from the skincare business in Indonesia, this research adds to the expanding body of literature on customer behaviour and brand management. Keywords: Product Quality; Brand Image; Purchase Decisions